Bryodiversity in the tropics: taxonomy of Microporella species (Bryozoa, Cheilostomata) with personate maternal zooids from Indian Ocean, Red Sea and southeast Mediterranean - Harmelin, Jean-Georges; Ostrovsky, Andrew N.; Cáceres-Chamizo, Julia P.; Sanner, Joann (Zootaxa, 2011)
The particularly speciose cheilostomate genus Microporella includes taxa whose maternal zooids and associated ovicells present a personate structure, i.e. a particularly developed peristome. Six species of Microporella with personate ovicells are analysed from material sampled in the Indian Ocean, Red Sea and southeast Mediterranean. Consideration of highly diagnostic tiny morphological characters displayed by the primary orifice and the avicularium has made it possible to distinguish three new species, M. browni n. sp., M. maldiviensis n. sp. and M. collaroides n. sp., and to better characterise the other species. Among the latter, two species named by Audouin (1826) from Savigny’s drawings (1817), M. coronata and M. genisii, are redescribed and neotypes are selected. Additionally, a new species of the M. coronata species group, Microporella hastingsae n. sp., is proposed following examination of a museum specimen recorded as M. ciliata var. coronata (Hastings 1927). The species dealt with in this study revealed remarkably different patterns of geographic distribution, possibly showing different potential for natural and/or anthropogenic dispersal. The bryozoan assemblages sampled along the coast of Lebanon include four of the six studied species, at least three of them presumably non-indigenous including M. harmeri Hayward, which displays a remarkably wide distribution from the Indian Ocean to the West Pacific and the East Atlantic (Canary Islands).